2021
DOI: 10.1186/s12891-021-04113-y
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods survey to explore issues with virtual consultations for musculoskeletal care during the COVID-19 pandemic

Abstract: Objective To explore orthopaedic and musculoskeletal clinicians’ views and experiences of legal, safety, safeguarding and security issues regarding the use of virtual consultations (VC) during the COVID-19 pandemic. A secondary objective was to suggest ways to overcome these issues. Methods A mixed method cross-sectional survey was conducted, seeking the views and experiences of orthopaedic and musculoskeletal medically qualified and Allied Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…Fifty-nine articles met the inclusion criteria and were considered for the analysis. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 The excluded thirty-four papers were editorials, letters, duplicate entries, and articles with no discussion on telemedicine even in the full text ( Figure 1 ). The monthly contributions trend of the orthopaedic telemedicine-related articles is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-nine articles met the inclusion criteria and were considered for the analysis. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 The excluded thirty-four papers were editorials, letters, duplicate entries, and articles with no discussion on telemedicine even in the full text ( Figure 1 ). The monthly contributions trend of the orthopaedic telemedicine-related articles is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Gilbert et al. 33 observed that teleconsultations had been rapidly deployed since the onset of the COVID-19 pandemic, often without clear guidance or consensus on many important issues. They identified legal and security issues in telemedicine implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of models such as virtual clinics is completely re-designing the concept of care, offering a viable, efficient approach to treat a variety of pediatric musculoskeletal disorders, but this needs further studies, especially regarding legal, safeguarding, safety and security issues. [ 18 , 19 , 20 , 21 ]. Another and more worrying explanation could be that, while the overall volumes of trauma patients decreased, the injury pattern changed, as reported in recent studies concerning adult trauma [ 13 , 14 ], thus requiring hospitalization more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…VC may lead to safeguarding issues through not being able to know, or control who was present at a consultation and it is important to ensure safeguarding policies at institutions consider issues arising from the use of VC. 30 Thorough evaluation of the effectiveness and safety of virtual management of patients is required to guide ongoing implementation moving forwards. Our work on rapid implementation found that, of the patients who underwent a video call, 44% of these would opt for a video for their next apppointment.…”
Section: Commentarymentioning
confidence: 99%